2011
DOI: 10.1182/blood-2011-04-351817
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rac GTPase signaling and downstream prosurvival Bcl-2 proteins as combination targeted therapy in MLL-AF9 leukemia

Abstract: The Rac family of small Rho GTPases coordinates diverse cellular functions in hematopoietic cells including adhesion, migration, cytoskeleton rearrangements, gene transcription, proliferation, and survival. The integrity of Rac signaling has also been found to critically regulate cellular functions in the initiation and maintenance of hematopoietic malignancies. Using an in vivo gene targeting approach, we demonstrate that Rac2, but not Rac1, is critical to the initiation of acute myeloid leukemia in a retrovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
63
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 50 publications
6
63
0
Order By: Relevance
“…56 Concurrent exposure to NSC-23766 increased the apoptotic effect of the Bcl-2 inhibitor and BH3 mimetic ABT-737 in leukemia cells. 57 Bcl-2 overexpression is a hallmark of CLL 58 . Coherently, BH3 mimetics have proven to be efficient in patients with CLL, but with heterogeneity, 59 and in microenvironmentmediated drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…56 Concurrent exposure to NSC-23766 increased the apoptotic effect of the Bcl-2 inhibitor and BH3 mimetic ABT-737 in leukemia cells. 57 Bcl-2 overexpression is a hallmark of CLL 58 . Coherently, BH3 mimetics have proven to be efficient in patients with CLL, but with heterogeneity, 59 and in microenvironmentmediated drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The MLL fusion protein MLL-AF9 immortalizes CB cells in vitro and produces human leukemia in immunodeficient mice (20). These engineered pre-leukemic and leukemic cells recapitulate many features of the clinical diseases and have been useful in testing different therapeutic strategies (21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…The dysregulated genes in Runx1/Cbfb-deleted cells contained several known RUNX1 targets, including RUNX1 itself and C/EBPα (Supplemental Tables 3 and 4). Among these candidate Runx target genes, we focused on Bcl2, which was shown to be important for the pathogenesis of MLL fusion leukemia (22,36). It was also shown that RUNX1 binds to the TGTGGT sequence in the BCL2 promoter (37).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that progression of preleukemic to leukemic MLL fusion cells involves increased canonical Wnt signaling 16 and Rac GTPase activation 17 ; both of these signaling pathways play critical roles in leukemia progression. 10,16,[18][19][20] The sensitivity of MLL-rearranged AML cells to Rac inhibition suggests that targeting Rac activity or signaling pathways leading to Rac activation may represent novel therapeutic opportunities. In support of this, pharmacologic Rac inhibition was found to interfere with leukemic engraftment of MLL-rearranged human AML cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…57,58 In MLL-rearranged AML, the importance of Rac activation to the leukemogenic function of MLL fusions has also been recently demonstrated. 10,19,20 By identifying the mediators of MLL fusioninduced Rac activation, the present study offers new candidates for novel therapeutic targeting. The inhibition of leukemic progression and Rac activation by FRATN suggests that targeting the FRAT2/ DVL/GSK3␤ axis would be an effective means of interfering with MLL fusion activity.…”
mentioning
confidence: 99%